Understanding Subaltern responses to biopiracy propagated by global patent laws post 1994 - Simane, Charles (My University, 2020)
Indigenous knowledge is not primitive. Indigenous knowledge of biodiversity is not the common heritage of mankind, it is the common heritage of the community to which it belongs. Indigenous people own what they know. Central to the logic of colonisation is the claim of ownership, either through assertions of terra nullius land or through claims of discovery with total disregard and no acknowledgement of prior knowledge by local people (Mignolo 2009). Contrary to colonial notions of ‘discovery’, it was not the Spaniards who discovered the potato, it was the Inca in modern day Peru (Zuckerman 1999). The Spanish merely brought it back to Europe as a cheap staple that could feed the work force required for the industrial revolution. The scenario is similar for tobacco. It was cultivated for centuries before the arrival of Europeans in South America, in fact, James Cook was offered the tobacco to smoke as a gift by the local people who had been smoking it for centuries (Zuckerman 1999). After being introduced to Europe, the tobacco became a huge sales success and quickly became the largest export from South America fuelling colonization and the introduction of African slave labour to meet the growing European demand for Tobacco. Although the tobacco grew in their lands, it was no longer theirs, it was now the property of a western company such as Lorillard Inc. Their indigenous knowledge which introduced the tobacco to the Europeans was appropriated and exploited without any form of compensation to them or regard for the centuries of selective breeding and the cultivation they had done. Through an ecofeminist lens, this research will explore the subaltern responses to this expropriation of indigenous knowledge of biodiversity
A research report submitted in partial fulfilment of the degree of Master of Arts in International Relations in the Faculty of Humanities at the University of the Witwatersrand, 2020